Digestive System Involvement During Coronavirus Disease 2019; the Newest Clinical Features and Potential Mechanisms - Jooya , Parisa; Najafi Kashkooli , Aida; Navari , Farzaneh; Gorjizadeh, Neda; Poudineh, Maryam; Pouralimohamadi , Neda; Asadian, Asma; Sabet , Hamidreza (Galen Medical Journal, 2022)
The coronavirus disease 2019 (COVID-19), which is caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has been recognized as a worldwide pandemic and mostly affects the respiratory system. A considerable proportion of patients; however, might also experience gastrointestinal (GI) manifestations. Several investigations have assessed GI and hepatic involvement in this disease, although the mechanisms of these involvements in relation to the progression of COVID-19 remain unclear. This review summarized the clinical observations and the main mechanisms behind GI, liver, and pancreatic involvement among COVID-19 patients.